Geodetic Monitoring for Land Deformation - Ng, Alex Hay-Man; Ge, Linlin; Chang, Hsing-Chung; Du, Zheyuan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on original research articles on the use of geodetic measurement techniques for land deformation identification, monitoring, and impact assessment. The development and application of modern surveying techniques for understanding land deformation is of particular interest. There is a special focus on examining the current and advanced geodetic measurement techniques, including radar interferometry (InSAR), global navigation satellite systems (GNSS), light detection and ranging (LiDAR), close-range photogrammetry (CRP), Robotic Total Station (RTS), digital levelling etc., to detect and monitor land deformation.